Using reflected signal power from the BeiDou geostationary satellites to estimate soil moisture. Issue 1 (2nd January 2019) - Yan, SongHua; Zhang, Nan; Chen, NengCheng; Gong, JianYa
ABSTRACT: Satellites-based microwave sensors are sensitive to soil moisture at the surface of the Earth, but their performance is limited by their continuously varying footprints due to the repeat cycle of satellites. In recent years, Global Navigation Satellite System (GNSS) microwave signals have been used to estimate soil moisture and the BeiDou system (BDS) provides new signal sources. Unlike Global Positioning System, BDS includes five geostationary earth orbit (GEO) satellites. Because their orbits are geosynchronous, the footprints of the GEO satellites remain nearly unchanged for fixed receivers; this property is beneficial for continuous long-term observation of reflection studies in the fixed area. We conducted a ground-based field experiment and collected data that included signals from GEO satellites and in situ soil moisture observations during this experiment to investigate the soil moisture estimation using the power of the reflected BDS signals. In this letter, we first designed a filter to separate the effect of GEO slight motion on raw signal. We then calculated and calibrated reflection coefficient. Finally, we estimate the continuous soil moisture in the fixed area per half hour using the reflection coefficient. The results show that the estimated soil moisture changes are largely consistent with the in situ soil moisture data except rainy days in which soil moisture changes rapidly and the mean absolute error of the estimation is less than 2.37%. This experiment demonstrates that the BDS GEO satellites represent an important source of data for use in GNSS reflectometry.